The Rorschach Test Evaluation in Chronic Childhood Migraine: A Preliminary Multicenter Case–Control Study - Maria Esposito; Antonietta Messina; Vincenzo Monda; Ilaria Bitetti; Filomena Salerno; Francesco Precenzano; Simone Pisano; Tiziana Salvati; Antonella Gritti; Rosa Marotta; Serena Marianna Lavano; Francesco Lavano; et al. (Frontiers in Neurology, 2017)
ObjectAbout 1.2–3.2% of children at 7 years of age with increasing age up to 4–19% in adolescents are suffering from migraine without aura (MwA). The aim of the present study is investigating the personality style associated with children and adolescents affected by MwA, administrating the Rorschach test, and comparing with typical developing healthy controls (TD).Methods137 patients (74 males), aged 7.3–17.4 years (mean age 11.4, SD 3.02 years), affected by MwA according to the IHs-3 criteria. The Rorschach variables were treated as numerical variables and statistically tested with t-Student’s analysis.ResultsNo statistical differences were found between the MwA and TD for age (p = 0.55), and gender (p = 0.804). From the comparison between the two samples, MwA group shows lower W responses (p < 0.001), good quality W responses (p < 0.001), high frequency of detailed responses (p < 0.001), the presence of even minor form of good quality responses (p < 0.001), increased presence of animals answers (A%) (p < 0.001), more frequent trivial answers (Ban%) (p < 0.001).DiscussionRorschach interpretation pinpointed many interesting and, perhaps, peculiar aspects in our MwA population such as a trend predisposition for: analytical reasoning rather than synthetic, ease/practicality rather than creativity, oppositionality rather than external adaptation to the environment that may be interpreted as effect of general maladaptivity.